Real-time loop-mediated isothermal amplification for rapid detection of Enterocytozoon hepatopenaei - Cai, Shao-Xin (PeerJ, 2018)
BACKGROUND: Enterocytozoon hepatopenaei (EHP) is a newly emerged microsporidian parasite that causes retarded shrimp growth in many countries. But there are no effective approaches to control this disease to date. The EHP could be an immune risk factor for increased dissemination of other diseases. Further, EHP infection involves the absence of obvious clinical signs and it is difficult to identify the pathogen through visual examination, increasing the risk of disease dissemination. It is urgent and necessary to develop a specific, rapid and sensitive EHP-infected shrimp diagnostic method to detect this parasite. In the present study, we developed and evaluated a rapid real-time loop-mediated isothermal amplification (real-time LAMP) for detection of EHP. METHODS: A rapid and efficient real-time LAMP method for the detection of EHP has been developed. Newly emerged EHP pathogens in China were collected and used as the sample, and three sets of specificity and sensitivity primers were designed. Three other aquatic pathogens were used as templates to test the specificity of the real-time LAMP assay. Also, we compared the real-time LAMP with the conventional LAMP by the serial dilutions of EHP DNA and their amplification curves. Application of real-time LAMP was carried out with clinical samples. RESULTS: Positive products were amplified only from EHP, but not from other tested species, EHP was detected from the clinical samples, suggesting a high specificity of this method. The final results of this assay were available within less than 45 min, and the initial amplification curve was observed at about 6 min. We found that the amplification with an exponential of sixfold dilutions of EHP DNA demonstrated a specific positive signal by the real-time LAMP, but not for the LAMP amplicons from the visual inspection. The real-time LAMP amplification curves demonstrated a higher slope than the conventional LAMP. DISCUSSION: In this study, pathogen virulence impacts have been increased in aquaculture and continuous observation was predominantly focused on EHP. The present study confirmed that the real-time LAMP assay is a promising and convenient method for the rapid identification of EHP in less time and cost. Its application greatly aids in the detection, surveillance, and prevention of EHP.